Development of dynamic centrifuge models of underground structures near tall buildings. Issue 86 (July 2016) - Dashti, S.; Hashash, Y.M.A.; Gillis, K.; Musgrove, M.; Walker, M.
Abstract: A series of six centrifuge experiments was designed and conducted to assess the seismic influence of a mid to highrise building on adjacent shallow underground structures. The buildings modeled in this study (12 and 42 stories) were the tallest structures tested in centrifuge to date. In designing these experiments, it was important to represent the modal frequencies, base shear, base moment, and yield characteristics of realistic mid and highrise structures, in order to transmit realistic seismic demands onto the underground structures. For the midrise structure, it was possible to simulate the height, mass, and three primary modes of response with a simplified, scaled model in centrifuge. For the highrise structure, additional simplifications were necessary due to a limited overhead space. A scaled, single-degree-of-freedom structure could capture the fundamental frequency, mass, and therefore base shear of a representative 42-story highrise building, while other properties were sacrificed. The six experiments with varied payloads required similar base motions to experimentally evaluate the seismic impact of buildings on underground structures. The heavy structures applied an unprecedented demand on the shaking table under increased gravity, which was expected to adversely affect the repeatability of motions. Even though the achieved base motions were significantly de-amplified compared to those desired, their coefficient of variation among six experiments was less than 0.2 in the frequency range of interest (0.2–5 Hz), indicating acceptable repeatability. The buildings were instrumented during the centrifuge tests to measure their base shear and roof drifts. The results were consistent with pushover analyses and design requirements, indicating realistic overall stiffness, yielding characteristics, and shear forces transmitted to the foundation. The overall response of the system indicates that, with reasonable approximations, the seismic forces transferred from tall buildings to the foundation soil and an adjacent underground structure can be successfully modeled and evaluated in centrifuge. Highlights: Scaled models of midrise and highrise buildings were designed in centrifuge. The scaled buildings needed to transmit realistic seismic demands onto foundation. The height, mass, and three primary modes of the midrise structure were modeled. The fundamental frequency, mass, and base shear forces of a highrise were modeled. Seismic forces from tall buildings could be modeled with reasonable approximations.